1991
DOI: 10.1002/cne.903140408
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin and calbindin localization in retina from six vertebrate species

Abstract: Calmodulin is abundant in the central nervous system, including the retina. However, the localization of calmodulin in the retina has not been described in detail. We therefore decided to investigate calmodulin localization in retinae from six vertebrate species, by using immunohistochemical labeling with four different rabbit polyclonal antibodies against calmodulin. The localization of calbindin-D28k, another calcium-binding protein already well described in retina, was compared. We found that calmodulin dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
3
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 33 publications
6
85
3
3
Order By: Relevance
“…Pochet et al (45) reported lack of immunoreactivity in mouse photoreceptors, which fits well with the very weak CaM signal in ONL and inner and outer segments in this study. On the other hand, CaM was detected in feline and bovine OS by ultrastructural immunostaining and biochemical methods, respectively (67,68).…”
Section: Discussionsupporting
confidence: 92%
“…Pochet et al (45) reported lack of immunoreactivity in mouse photoreceptors, which fits well with the very weak CaM signal in ONL and inner and outer segments in this study. On the other hand, CaM was detected in feline and bovine OS by ultrastructural immunostaining and biochemical methods, respectively (67,68).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, calcineurin not only binds calcium but is regulated by a most representative Ca ϩϩ -binding protein, CaM. Among the Ca ϩϩ -binding proteins whose presence has been shown by immunohistochemistry in various retinal cells (ganglion and amacrine but, specifically, neither photoreceptor nor Müller cells) are CaM (Seto-Ohshima et al 1987;Pochet et al 1991), calbindin D-28k (Uesugi et al 1992), parvalbumin (Endo et al 1985), calretinin (Bastianelli et al 1995), and neurocalcin (Nakano et al 1992). Another Ca ϩϩ -binding protein, recoverin, is exceptional because it is located mainly in photoreceptor and bipolar cells (Korf et al 1992;Günhan-Agar et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the specificity of the generated conditional mutation, the former possibility is unlikely. Specifically, an alteration of the properties of retinal bipolar cells, which are known to express L7/pcp-2 and the Cre transgene used in this study (Barski et al, 2000), can be excluded, because calbindin is not expressed in these cells in mice (Celio, 1990;Pochet et al, 1991). These data show that absence of calbindin from cerebellar Purkinje cells affects eye (as well as limb) coordination and suggest that calbindin in these cells is important for differential regulation of calcium signals involved in processing of visual and vestibular information.…”
Section: Compensatory Eye Movementmentioning
confidence: 99%